Nickel‐Catalyzed Arylation, Alkenylation, and Alkynylation of Unprotected Thioglycosides at Room Temperature. Issue 45 (24th September 2013) - Brachet, Etienne; Brion, Jean‐Daniel; Alami, Mouad; Messaoudi, Samir
Abstract Unprotected thioglycosides were effective nucleophiles for Ni0‐catalyzed CS bond‐forming reaction with functionalized (hetero)aryl, alkenyl, and alkynyl halides. The functional‐group tolerance on the electrophilic partner was typically high and the anomeric selectivities of the thioglycosides were high in all cases. The efficiency of this general procedure was well‐demonstrated by the synthesis of 4‐methyl‐7‐thioumbelliferyl‐β‐D‐cellobioside (MUS‐CB).